Visualization of Proximal and Distal Kaplan Fibers Using 3-Dimensional Magnetic Resonance Imaging and Anatomic Dissection. Issue 8 (July 2020) - Berthold, Daniel P.; Willinger, Lukas; Muench, Lukas N.; Forkel, Philipp; Schmitt, Andreas; Woertler, Klaus; Imhoff, Andreas B.; Herbst, Elmar
Background: In current magnetic resonance imaging (MRI) of the knee, injuries to the anterolateral ligament complex (ALC) and the Kaplan fibers (KFs) are not routinely assessed. As ruptures of the KFs contribute to anterolateral rotatory instability in the anterior cruciate ligament–deficient knee, detecting these injuries on MRI may help surgeons to individualize treatment. Purpose: To visualize the KFs on 3-T MRI and to conduct a layer-by-layer dissection of the ALC. Study Design: Descriptive laboratory study. Methods: Ten fresh-frozen human cadaveric knees (mean ± SD age, 72 ± 8.5 years) without history of ligament injury were used in this study. Before layer-by-layer dissection of the ALC, MRI was performed to define the radiologic anatomy of the KFs. A coronal T1-weighted 3-dimensional turbo spin echo sequence and a transverse T2-weighted turbo spin echo sequence were obtained. Three-dimensional data sets were used for multiplanar reconstructions. Results: KFs were identified in 100% of cases on MRI and in anatomic dissection. The mean length of the proximal and distal KFs was 17.9 ± 3.6 mm and 12.4 ± 6.5 mm, respectively. On MRI, the distance from the lateral femoral epicondyle to the proximal KFs was 35.9 ± 6.9 mm and to the distal KFs, 16.6 ± 4.1 mm; in anatomic dissection, the distances were 41.4 ± 8.1 mm for proximal KFs and 28.2 ± 8.1 mm for distal KFs. The distance from the lateral joint line to the proximal KFs was 63.5 ± 7.6 mm and to the distal KFs, 45.3 ± 3.7 mm. Interobserver reliability for image analysis was excellent for all measurements. Conclusion: KFs can be consistently identified on MRI with use of 3-dimensional sequences. Subsequent anatomic dissection confirmed their close topography to the superior lateral genicular artery. For clinical implications, the integrity of the KFs should be routinely reviewed on MRI scans Clinical Relevance: As ruptures of the KFs contribute to anterolateral rotatory instability, accurate visualization of the KFs on MRI may facilitate surgical decision making for additional anterolateral procedures in the anterior cruciate ligament–deficient knee.